Нepatoprotective еffects of lithium ascorbate on a model of nonalcoholic fatty liver disease with iron overload - T. E. Bogacheva; A. G. Kalacheva; O. A. Gromova; I. Yu. Torshin; T. R. Grishina; A. A. Garanin (Фармакокинетика и Фармакодинамика)
Lithium ascorbate is a lithium salt with normothymic and neuroprotective properties. In an experimental model of non-alcoholic fatty liver disease with multiorgan pathology caused by combined consumption of excessive amounts of saturated fats, carbohydrates and inorganic iron salt, the use of lithium ascorbate showed pronounced hepatoprotective effects. The introduction of lithium ascorbate reduced the level of ferritin and transferrin saturation, the content of serum iron, AST, ALT, serum creatinine, leukocytes and normalized the level of serum protein and the rate of glomerular filtration. Lithium ascorbate reduced the increased content of reticulocytes and platelets to control values, restored the levels of vitamins C, B12 in the blood and reduced the number of Kupffer cells in the liver, which were overloaded with iron. The hepatoprotective effect of lithium ascorbate was confirmed histologically. The ability of the neuroprotector lithium ascorbate to reduce the level of hemosiderosis can be used in the treatment of patients with hepatic encephalopathy.